1998
DOI: 10.1046/j.1460-9568.1998.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for functional native NMDA receptors activated by glycine or d‐serine alone in the absence of glutamatergic coagonist

Abstract: In this study we have examined the effects of N-methyl-D-aspartate (NMDA) receptor activation on the release of cholecystokinin and somatostatin from rat neocortical nerve endings. The release of cholecystokinin-like immunoreactivity (CCK-LI) and of somatostatin-like immunoreactivity (SRIF-LI) elicited by 12 mM K+ from superfused synaptosomes, but not the spontaneous release, was increased by NMDA in a concentration-dependent manner. The effects of NMDA could be prevented by antagonists selective for the gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 58 publications
2
33
1
Order By: Relevance
“…Many studies have reported trace glycine contamination of buffer solutions, ranging from 10 to 50 nM (Johnson and Ascher, 1987;Lerma et al, 1990;Zhang et al, 1997;Paudice et al, 1998). In our glycine concentration-response experiments, WT receptors exhibited no response to 10 nM glycine in the presence of 100 M glutamate (0.00 Ϯ 0.00; Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Many studies have reported trace glycine contamination of buffer solutions, ranging from 10 to 50 nM (Johnson and Ascher, 1987;Lerma et al, 1990;Zhang et al, 1997;Paudice et al, 1998). In our glycine concentration-response experiments, WT receptors exhibited no response to 10 nM glycine in the presence of 100 M glutamate (0.00 Ϯ 0.00; Fig.…”
Section: Resultsmentioning
confidence: 62%
“…More likely, synaptosomal NMDARs in Mg 2ϩ -free medium were already activated. Activation of NMDARs on noradrenergic terminals occurs by simply removing Mg 2ϩ from the medium (Paudice et al, 1998). Moreover, the preparation of synaptosomes itself leads to their partial depolarization (Saller and Salama, 1984), and activity of NR2B- Up to now, histamine was considered to interact with the polyamine site of the NMDAR (Brown et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Because exogenous D-serine potentiates NMDA receptormediated neurotransmission (8)(9)(10)(11)) and D-[ 3 H]serine selectively binds to the glycine site (6), D-serine has been proposed as an endogenous ligand for the strychnine-insensitive glycine site of the NMDA receptor (6). Activation of NMDA receptors requires the presence of a coagonist, initially thought to be glycine (8,(12)(13)(14), and a glycine-selective recognition domain has been localized on NMDA receptors (15)(16)(17).…”
mentioning
confidence: 99%